Keterkaitan Produksi dan Konsumsi Telur Ayam Ras dalam Memenuhi Kebutuhan Pangan Hewani di Sulawesi Selatan - Nurul Fatimah Syam; Ahmad Ramadhan Siregar; Ariady Arsal (Jurnal Galung Tropika, 2024)
The research aims to analyze the factors that influence production and consumption and the relationship between the production and consumption of purebred chicken eggs in meeting animal food needs in South Sulawesi. The methods used in this research are descriptive analysis method and quantitative analysis. The sample in this research was 120 breeders and household consumers. The data collected is primary and secondary. Primary data was obtained from respondents through observation, interviews, and distribution of questionnaires. Primary data processing uses the SEM-PLS (Structural Equation Modeling-Partial Least Square) method. Secondary data was obtained from the Central Statistics Agency, Livestock Service, and South Sulawesi Agricultural Extension Center. The research results show that the R-squared value of egg production is 0.792. This value shows that feed, DOC, labor, and capital have a positive and significant effect on egg production of 79.2%. Furthermore, the R-squared value of egg consumption is 0.812. This value shows that price, income, population, and taste positively and significantly affect egg production by 81.2%. Furthermore, the R-Square value of Fulfillment of Animal Needs is 0.530, which means that Egg Consumption and Egg Production can explain or influence positively and significantly the Fulfillment of Animal Needs by 53% with a production coefficient value of ?= 0.479 > Consumption coefficient ?= 0.478.